EARTH AND MARS CULTURE INANDREw STANTON'S MOVIE "JOHN CARTER OF MARS" (SOCIOLOGICAL APPROACH) - Arina Iskandar; Serliah Nur; Nasrum Nasrum (Elite : English and Literature Journal, 2016)
This thesis studied about culture based on the script of the movie John Carter of Mars which was released in 2012. This research aimed to describe and analyze the kinds and comparison on Earth and Mars culture in the movie. This research focused on sociological approach and culture based on Edward B. Tylor and Hofstede's theories toward kinds of culture elements. This research used descriptive qualitative method and used note taking as the instrument. The findings showed that there were twenty-two kinds of data reffered to culture elements which were divided into seven categories; knowledge religion, art, morals, laws, customs, and language. Thus, there were twenty-two which were divided into ten data on Earth and twelve data on Mars. Therefore, the researcher concluded that seven culture elements were the shaper element toward the societies activity on Earth and Mars based on John Carter of Mars movie that became the distinguishing appropriate with their respective ways.